ANALISIS NILAI-NILAI MODERASI BERAGAMA DALAM KEGIATAN EKSTRAKURIKULER HIMPUNAN AKTIVIS MASJID ASSALAM (HAMAS) DAN IMPLIKASINYA TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (Studi Kasus SMAN 5 Kota Tasikmalaya) - Yusuf Anggia, Iqbal; Anggia Yusuf, Iqbal; Devi Lestari (HASBUNA : Jurnal Pendidikan Islam, 2023)
This study aims to discuss the values ​​of religious moderation in HAMAS (Assalam Mosque Activist Association) extracurricular activities and their implications for learning Islamic Religious Education (Research Study at SMAN 5 Kota Tasikmalaya). starting from the framework of thinking that the presence of religious moderation in Indonesia is one of the important arguments, considering that students in schools are very diverse and multicultural. Religious moderation is carried out to avoid radicalism and extremism in Islamic religious teachings. Based on the background of the problem, the author will conduct research on religious extracurricular activities in schools. In this study the authors used a qualitative descriptive method, namely the researcher provided an overview or described the results of the observations obtained from the collected data and then analyzed and explained in words, events, activities. The aims of this study were (1) To find out the values ​​of religious moderation in HAMAS (Assalam Mosque Activists Association) extracurricular activities at SMAN 5 Tasikmalaya City (2) To find out the relevance of religious moderation values ​​to HAMAS (Mosque Activists Association) extracurricular activities Assalam) at SMAN 5 Tasikmalaya City with Islamic Education (3) To find out the implications of religious moderation values ​​in HAMAS (Assalam Mosque Activist Association) extracurricular activities at SMAN 5 Tasikmalaya City for learning Islamic Religious Education.